The narrative in the discourse of the Iraqi economic journalism A semiotic approach to analyzing a news text in A almada newspaper - Al- Kemawee Jaafar Abd Al Hussain Kahdhim (Genius Journals, 2024)
The economic journalism discourse is one of the types of narratives in the specialized media discourse, through which the communicator seeks to narrate the details of his communication message according to a narrative program, in an effort to convince the recipient and then the intended effect occurs in it, the research included a theoretical entry about the narrative in the journalistic discourse and the importance of the semiotic analysis of journalistic news texts, according to a set of pivotal steps in an effort to reach the meanings inherent in the text, News texts represent non-imaginary media narrative texts that can be subjected to semiotic analysis, semiotic analysis of texts includes semiological anaiosis) among the methodological tools used in discourse analysis, semiotic analysis It relies on the analysis of the symbolic system of all kinds, forms and tools to explore the significance behind it, as it does not stop at the limits of analysis, but goes beyond that, trying to explore the meanings behind it and express it . The research has reached a set of results, the most prominent of which are: 1-the narrator (the writer of the news) used the moderate pyramid template in narrating the details of the news report, (introduction, body details, and conclusion) in an effort to provide the successive narration of the events of the text.
Keywords: narration; beyond; semiotic analysis; methodological